Competition between the Hydride Ligands of Two Types in Proton Transfer to [{κ3‐P‐CH3C(CH2CH2PPh2)3}RuH(η2‐BH4)] - Golub, Igor E.; Filippov, Oleg A.; Belkova, Natalia V.; Gutsul, Eugenii I.; Epstein, Lina M.; Rossin, Andrea; Peruzzini, Maurizio; Shubina, Elena S. (European journal of inorganic chemistry, 2017)
The interaction of the mixed hydrido–tetrahydridoborate ruthenium(II) complex [(Triphos)RuH(η2‐BH4)] [1; Triphos = κ3‐P‐CH3C(CH2CH2PPh2)3] with alcohols of variable acidic strength [MeOH, FCH2CH2OH (MFE), CF3CH2OH (TFE), (CF3)2CHOH (HFIP), and (CF3)3COH (PFTB)] was the subject of a combined computational (DFT) and spectroscopic (VT FTIR, NMR) study. The experimental spectra suggests that RuH···HO bond formation precedes the protonation of 1, and H2 evolution leads to the loss of boron and the formation of the dimetallic [{(Triphos)RuH}2(µ,η2:η2‐BH4)]+ cation. The experimentally determined basicity factor [Ej(RuH)] of the Ru‐bound hydrido ligand of 1.43 is among the highest determined for ruthenium hydrides. Such high basicity leads to very easy proton transfer to the RuH ligand for strong alcohols (HFIP and PFTB). An alternative reaction pathway involving the migration of the bridging hydride (BHbr) to the ruthenium center is suggested for weaker proton donors (MeOH and TFE). The basicity factor of the Ru‐bound hydrido ligand of [(Triphos)RuH(η2‐BH4)] [Triphos = κ3‐P‐CH3C(CH2CH2PPh2)3] is among the highest determined for ruthenium hydrides. Such high basicity leads to very easy proton transfer to the Ru–H moiety for strong alcohols. An alternative reaction pathway involving bridging hydride migration to the ruthenium center is suggested for weaker proton donors.